Australian Housing and Urban Research Institute AHURI - Rowley, Steven; Costello, Greg; Higgins, D.; Phibbs, P. (Australian Housing and Urban Research Institute, 2014)
A significant issue for both housing and urban policy is an adequate supply of housing to accommodate the current and projected demand for housing. The National Housing Supply Council has highlighted the serious shortfall between housing supply and demand from households (NHSC 2012). While there are various reasons for this undersupply, a key but often overlooked consideration is the financing of residential developments. In most cases, without financing (debt, equity or some combination), residential development is not possible (Miles et al. 2007).